MARKETING SECTOR DEVELOPMENT AS SUPPORT FOR FISHERIES INDUSTRIALIZATION (CASE STUDY: TILAPIA FISH IN MUSI RAWAS DISTRICT, SOUTH SUMATRA) - Hertria Maharani (Pusbindiklat - LIPI, 2015)
Fisheries industrialization announced by the Ministry of Marine and Fisheries Affairs aims to increaseproduction, productivity, and value added of fishery products. However, increased production without increasingmarketingefforts will make less successful impact for the program. This research examines the aquaculture, market,channel marketing, and trading of tilapia from Musi Rawas, South Sumatra. Field studies were conducted inMarch–June 2012. Survey method was used as the main instrument of this study, with the help of questionnairesand in-depth interviews with key informants. Respondents consisted of farmers, collectors, traders, and policymakers related tilapia. Descriptive analysis was conducted for the method of analysis. Results of the study showedthat despite an increase in production experienced by farmers, commodities are marketed only to the local market.Farmers are still the price takers which means they cannot increase the bargaining power. The structure of farmersmarkets are perfectly competitive, while the structure is oligopsonistic merchant. So the prices at the level of farmersare controlling nature merchants. To improve the welfare of farmers aquaculture, should diminishing patronclient relationship and search for new marketing channels need to be done as the customer looking for a restaurantor doing marketing tilapia up to another area.